Uveal melanoma: management and outcome of patients with extraocular spread. Issue 5 (3rd December 2009) - Bellmann, Caren; Lumbroso-Le Rouic, Livia; Levy, Christine; Plancher, Corine; Dendale, Remi; Sastre-Garau, Xavier; Asselain, Bernard; Desjardins, Laurence
Abstract : Background: Extraocular spread is thought to be a negative prognostic factor on the survival in patients with uveal melanoma. Enucleation was the standard treatment in these patients. Today, depending on the size of the tumour and the type of extraocular extension, eye-preserving irradiation treatments, such as proton beams or radioactive plaques, may be employed. Methods: 2256 patients were treated between 2000 and 2007 at the Institut Curie, Paris, France for a uveal melanoma. 67 patients (3.0%) presented an extraocular extension. A retrospective study was performed to evaluate the patients' outcomes with regard to tumour recurrence and survival. Results: Eye-conserving treatment was employed in 38 (52.8%) patients. Enucleation was performed in 29 (47.2%) patients. The median follow-up was 38 (range 7 to 79) months with an overall survival rate at 5 years of 40.4% in enucleated patients and 79.3% in the eye-conserving treatment group (protons n=19, iodine-125 plaque n=19) (p=0.01; Kaplan–Meier analysis). No tumour recurrence was observed in any group. The degree of extraocular spread as well as the clinical characteristics tumour location, retinal detachment, ciliary body involvement (p<0.01; χ 2 test) and tumour thickness (p=0.04; χ 2 test) influenced the choice of treatment. Age, tumour diameter, involvement of optic nerve, vitreous haemorrhage and the amount of pigment did not have any influence. Conclusions: Tumour recurrence rates and survival rates were not adversely affected in patients receiving conservative eye treatment. This may thus represent a therapeutic option in certain patients with extraocular spread.